A help for assisting people based on a depth cameras system dedicated to elderly and dependant people - Ben Hadj Mohamed, Asma; Val, Thierry; Andrieux, Laurent; kachouri, Abdennaceur (British Journal of Healthcare and Medical Research, 2015)
In this paper, we propose a help to a comfort system development based on Kinect sensor to assist people commanding their own house by using only their gestures. The system uses the sensors to detect the person, recognize her gestures and communicate through an IP/KNX gateway to act on actuators related to the home. Thus, a simple gesture is able to turn on/off the lights, to switch on/off the TV, to move up or down the shutters etc. We performed a test bed within the smart home of our University Institute of Technology in Blagnac.